Effect of proline-rich polypeptide on various lines of tumour cells, normal bone marrow and giantcell tumour stromal tissue - Chailakhyan, R.K.; Galoyan, A.A.; Gerasimov, Yu.V.; Stepanova, E.V.; Chailakhyan, M.R.; Solomko, E.Sh. (Вiopolymers and Cell, 2011)
The aim of the study was to assess the effect of proline-rich polypeptide (PRP) on bone marrow stromal stem cells in vivo and in vitro and on tumour cell lines. Methods. Isolation of giant-cell tumour (GCT) stromal cells and obtaining these cell strains; obtaining normal bone marrow stromal cell strains; PRP administration to rats; bone marrow cell explantation into cultures; PRP addition to cell cultures. Results. Various routes and doses of PRP administration to rats increased the multipotent mesenchymal stromal cell (MMSC) concentration in the bone marrow. PRP addition to normal bone marrow MMSC cultures increased cell proliferation 1.5– 2.5-fold, whereas PRP addition to GCT MMSC cultures inhibited cell proliferation 1.5–2-fold. Both proliferation inhibition and no PRP effect on proliferation were observed in tumour cell cultures. Conclusions. PRP administration to rats increased MMSC concentration in the normal bone marrow, and PRP addition to tissue cultures revealed opposite effects of PRP on cell proliferation. Keywords: Proline-rich polypeptide (PRP), multipotent mesenchymal stromal cells (MMSC).